Cone-beam CT measurement of root canal diameter and taper for mandibular first molar - LI Wenmiao; XING Li; PAN Yingyu; HUANG Ying; YANG Guofang; LIU Deda (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To analyze the root canal diameter and taper of mandibular first molars using cone-beam CT (CBCT), investigate age-related changes in these parameters, and propose optimized clinical protocols for root canal preparation.Methods·From October 2022 to October 2023, CBCT images of 240 healthy mandibular first molars (120 three-canal type cases and 120 four-canal type cases) were collected from patients aged 20‒59 years at the Stomatology Center, Haikou Affiliated Hospital of Central South University Xiangya School of Medicine. The three-canal type and the four-canal type samples were respectively divided into four age groups (20‒29, 30‒39, 40‒49, and 50‒59 years), with 30 cases in each group. Root canal length was measured, and buccolingual and mesiodistal diameters were recorded at four levels (coronal, middle, apical, and foramen). The tapers of the coronal 1/3, middle 1/3, and apical 1/3 segments were calculated in both buccolingual and mesiodistal directions. Differences among the age groups were compared.Results·The buccolingual diameters of all root canals exceeded the corresponding mesiodistal diameters. At several levels of most root canals, the diameters in the <50-year-old groups were significantly larger than those in the 50‒59-year-old group (P<0.05). The buccolingual tapers exceeded the corresponding mesiodistal tapers in all root canals of mandibular first molars. The mean mesiodistal tapers in different age groups ranged from 0.07 to 0.34 in the coronal 1/3 segment, 0.03 to 0.09 in the middle 1/3 segment, and 0.05 to 0.11 in the apical 1/3 segment. At several levels of most root canals, the tapers in the <50-year-old groups were significantly larger than those in the 50‒59-year-old group (P<0.05).Conclusion·Mandibular first molars exhibit age-related narrowing of root canal diameter and reduced taper in individuals aged ≥50 years. For initial apical file selection, #15 files are recommended for the distal canals in the three-canal type, while #10 files are advised for all other canals in the three-canal type and all canals in the four-canal type. For patients aged 50 years or older, the files for the distal canals in the three-canal type can be adjusted to #10, and the files for the mesiobuccal and distallingual canals in the four-canal type to #8. Regarding preparation taper, a 0.08-taper orifice opener is recommended for the coronal 1/3 segment. During mid-lower segment preparation, 0.04-taper master apical files are suggested for the mesiobuccal and mesiolingual canals in the three-canal type and the mesiolingual and distallingual canals in the four-canal type, 0.06-taper files for the distal canals in the three-canal type and the mesiobuccal canals in the four-canal type, and 0.08-taper files for the distobuccal canals in the four-canal type. Root canal obturation is recommended to be performed using vertical compaction with large-taper gutta-percha cones combined with bioceramic sealer.